Características bromatológicas e perfil fermentativo da silagem de milheto forrageiro (pennisetun glaucum) aditivado com casca de soja - Silva, Renan Sousa da (2015)
The ensiling process is a much used alternative in animal husbandry systems, consisting in the preservation of moist forage, fresh-cut or pre-dried, with high nutritional value, to be administered in times of food shortages. Brazil is characterized by a strong seasonality and basically has two distinct seasons in some regions of the country, one high and one low rainfall. The tropical grasses used in Brazilian pastures lose their quality and produce less in times of drought and low temperatures. All these factors justify the use of silage technique. The objective of this study is to evaluate four different levels of inclusion of soybean hulls in millet forage silage in order to determine the nutritional increments that it provided, in addition to analyzing the fermentation process associated losses of the silage process. The bromotalógica composition was positively affected by the inclusion of soybean hulls, with .lineares increases in DM and CP levels. The NDF also an increase in the levels. The inclusion of soybean hulls in silage millet reduced losses by gases and effluents, keeping stable the recovery of dry matter. The ammonia levels were reduced with the addition of the additive. Soy hulls did not affect the lactic acid content, acetic and butyric within acceptable Nives no statistical difference. The work also revealed a slight decrease in propionic acid. The titratable acidity and pH levels of silage did not differ. Palavras Chaves: